F (x) = $\displaystyle 5^{-2x^2+x}$
Last edited by wopashui; Jan 30th 2010 at 03:11 PM.
Follow Math Help Forum on Facebook and Google+
The general rule for a constant raised to a function of x is: if $\displaystyle f(x)=a^{g(x)}$ then $\displaystyle f'(x) = g'(x) \cdot \ln(a) \cdot a^{g(x)}$ Can you apply the rule?
Originally Posted by wopashui F (x) = $\displaystyle 5^{-2x^2+x}$ Just apply the following: If $\displaystyle f(x)=a^{g(x)}$ where $\displaystyle a>0$. then: $\displaystyle f'(x)=a^{g(x)} g'(x) ln(a)$.
Originally Posted by General Just apply the following: If $\displaystyle f(x)=a^{g(x)}$ where $\displaystyle a>0$. then: $\displaystyle f'(x)=a^{g(x)} g'(x) ln(a)$. can you explain what F (x) is, it's not the same as f (x), isn't it?
Originally Posted by wopashui can you explain what F (x) is, it's not the same as f (x), isn't it? It is exactly the same. We could also write the function as $\displaystyle \phi (x), \epsilon (x), \mu (x), g(x), G(x), u(x), V(x)$ etc etc...
View Tag Cloud